Transparency in public sector institutions in Saudi Arabia - Al - Fawzan, Nasser bin Mohammed; al - Otaibi, Nada Bint Falah bin Qad (Journal of Economic, Administrative and Legal Sciences, 2017)
This study aimed to know the level of transparency in public organizations and the factors affecting the application of transparency, and attempting to reach the most important means and suggested mechanisms to develop and raise the level of transparency. To achieve the aim of this study the opinions of (managers – agents- heads of sections – supervisors) were reviewed where the choice was randomly made for (11) government ministries out of (22) government ministries in Riyadh to represent the public organizations> (356) employees were surveyed in these ministries with a response rate of about (71%). The study concluded that the level of administrative transparency application in the organizations that are investigated was moderate in general; where clarity represents the maximum available of transparency's dimensions, while participation in decision making represents the least available of the transparency's dimensions. The study also showed that there are factors that affect transparency's application. The command & training appeared to be the most effective factors in transparency's application where it appeared that the weak ability of leaders to determine the priorities of the goals required to be achieved, and the arrival of unqualified administrative leaderships to high posts in the organizations affect in transparency's application. Also the study concluded that the least effective factors on transparency's application are represented in low interest in technology, routine work, and complexity in procedures. The study also concluded that the most important methods and mechanisms to develop and raise the level of transparency's application in administration according to the opinion of those investigated are represented in the following: The development of a system to fight corruption, granting transparency prize to honor those who are distinguished, provision of a data base inside the organization, care for computer at work, and explaining the importance of transparency for employees. The study also showed the availability of an impact of statistical significance of the educational level variable on the opinion of employees regarding transparency's level in administration in government bodies in Riyadh city, where employees who are of high educational standard are of the opinion that transparency is practiced in government bodies more than those of low educational standard. This study concluded in several recommendations for boosting
Keywords: transparency; institutions; public sector; government